2014
DOI: 10.1021/ac5002965
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Lambda Exonuclease onto Polymer Micropillar Arrays for the Solid-Phase Digestion of dsDNAs

Abstract: The process of immobilizing enzymes onto solid supports for bioreactions has some compelling advantages compared to their solution-based counterpart including the facile separation of enzyme from products, elimination of enzyme autodigestion, and increased enzyme stability and activity. We report the immobilization of λ-exonuclease onto poly(methylmethacrylate) (PMMA) micropillars populated within a microfluidic device for the on-chip digestion of double-stranded DNA. Enzyme immobilization was successfully acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…In Figure a, the current reached a saturated value at high concentration of the hsDNA substrate, showing the characteristics of the Michaelis‐Menten kinetics. The K’ M determined in the study (Figure b) was calculated to be 90 nM which was close to the reported value for Exo III in homogeneous assay . These results revealed that there was no substantial loss of Exo III activity, indicating the method using electrochemical graphene utilization was comparable with other conventional approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure a, the current reached a saturated value at high concentration of the hsDNA substrate, showing the characteristics of the Michaelis‐Menten kinetics. The K’ M determined in the study (Figure b) was calculated to be 90 nM which was close to the reported value for Exo III in homogeneous assay . These results revealed that there was no substantial loss of Exo III activity, indicating the method using electrochemical graphene utilization was comparable with other conventional approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Only O 2 plasma activation was explored here because this is commonly used for the assembly of nanofluidic devices, and surface roughness can play a significant role in determining the functional properties of nanofluidic devices. 9, 12, 17, 25, 41, 46, 47 For these studies, the initial RMS surface roughness of native COC thermoplastics was measured using AFM. Then, each substrate was exposed to 30 s of 50 W O 2 plasma, as this treatment can serve as an effective strategy for thermal fusion bonding cover plates to thermoplastic substrates, 46 and the RMS roughness was re-measured following this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To address these issues, we are developing an innovative SMS strategy that enzymatically cleaves DNAs using a surface-immobilized processive exonuclease to generate the dNMPs [2426]. The released dNMPs are electrokinetically transported through a nanochannel and identification of the nucleobases is carried out using the unique apparent mobility ( i.e ., mobility matching) of each dNMP electrokinetically traveling through a nanochannel.…”
Section: Introductionmentioning
confidence: 99%